Guillain‐Barré Syndrome in Africa: Understanding, Addressing, and Empowering - Burhan Kantawala; Olivier Uwishema; Anamarija Minova; Jonathan Babuya; Essey Ketema Wodajo; Sucharu Asri; Magda Wojtara (Health Science Reports)
ABSTRACT Introduction Guillain‐Barré Syndrome (GBS) is a spectrum of peripheral neuropathies characterized by rapid symmetrical limb weakness and sensory symptoms. GBS can be life‐threatening and requires intensive care, particularly for patients with imminent respiratory failure. In Africa, limited research and high therapy costs pose challenges. This literature review aims to comprehensively address GBS in Africa to improve understanding and outcomes. Aim This literature review aims to provide an extensive overview of GBS in Africa, encompassing its clinical presentation, impact, management approaches, and challenges faced. It also highlights the need for increased research and awareness to enhance patient care and outcomes. Methods A comprehensive review of existing literature on GBS in Africa was conducted, focusing on clinical presentation, diagnosis, management, and its impact on patients and communities. Data sources included medical databases, research articles, and reports. Data was scoured from databases such as PubMed, Medline and Embase. A total of four hundred and fifty‐five articles and case studies were screened, with broader topic margins into GBS and different triggers, demographics, statistics, and variations in treatments across the world. These articles were further screened to match our inclusion criteria which focused on articles published after 2000 and which gave clearer insights into the presentations and situation of GBS in the African continent. Results GBS in Africa is characterized by a range of clinical presentations, with limited diagnostic resources and healthcare infrastructure. Patients often face long intervals between symptom onset and hospitalization, impacting outcomes. The syndrome's impact extends beyond physical symptoms, affecting patients' quality of life, employment, and community roles. Management involves immunotherapy, physiotherapy, and psychosocial support, but high therapy costs and incomplete recovery pose challenges. Research in Africa has grown in recent years but remains limited compared to other regions. Efforts are needed to expand research capacity, introduce early screening programs, and improve healthcare infrastructure. Conclusion GBS presents a significant healthcare challenge in Africa, with the potential for severe clinical outcomes. This literature review underscores the importance of enhancing research, awareness, and healthcare infrastructure. African‐led research initiatives offer hope for improved patient outcomes and healthcare system strengthening. By advocating for increased government support and resources, Africa can address the pressing needs of GBS patients and foster a brighter and healthier future for affected individuals on the continent.